The Effects of Petroleum Price on Consumer Price Index in Nepal: Through the Lens of an ARDL Approach - Lamsal, Mani Ratna (Economic Review of Nepal, 2024)
The uncontrolled and unexpected increase in inflation in the Nepalese economy has numerous consequences. Even though inflation in Nepal has been increasing each year due to increasing fuel prices; the relationship between petroleum prices and CPI inflation has not been amply studied yet. So, the major objective of this paper is to explore the effects of petroleum prices on the CPI inflation in Nepal. The Auto Regressive Distributed Lag (ARDL) Model is used in the study to explore the effects of petroleum prices on CPI inflation in Nepal. The time series data for 33 years, spanning 1990-2022, were collected from various sources such as Nepal Oil Corporation (NOC), Nepal Rastra Bank (NRB), and World Bank data. This study found a significant positive relationship between diesel prices and CPI inflation in Nepal. The impact of a broad money supply is positive and significant for CPI. However, there is a negative effect of World Oil Prices on CPI of Nepal. The government of Nepal and other concerned agencies should develop and apply appropriate fiscal and monetary policies to control the unexpected hike in the inflation rate in Nepal. An increase in inflation has numerous consequences, as it increases the cost of living and poverty in the nation. Thus, macroeconomic policies should be formulated to control inflation at a minimum rate in Nepal, as it is practiced in many other countries.